A machine of superlatives. Issue 12 (December 2018) - Tuning, Niels
The Large Hadron Collider has completed its second data-taking period. For the next two years, the accelerator will shut down and the experiments will undergo major upgrades. Here's a take on our past achievements — and a preview of the future.